Achieving and assuring high availability - Trivedi, Kishor; Ciardo, Gianfranco; Dasarathy, Balakrishnan; Grottke, Michael; Matias, Rivalino; Rindos, Andy; Vashaw, Bart (5th International Service Availability Symposium, 2008)
We discuss availability aspects of large software-based systems. We classify faults into Bohrbugs, Mandelbugs and aging-related bugs, then examine mitigation methods for the last two bug types. We also consider quantitative approaches to availability assurance. ©2008 IEEE.
WiSo-Import:2015-04-17:1492
Keywords: Innovation